Studies in albedo measurements at Pune - DESIKAN , V.; CHIVATE, V. R. (MAUSAM, 1990)
Reflected solar radiation measurements are being made regularly at Pune over bare soil. The variations in albedo for a selected period are discussed. The value of Aledo is strongly dependent on the to Dr. wetness of soil the change being of the order of 30 per cent. The changes In albedo due to diffuse radiation and for different types of cloudy conditions are also discussed, The presence of cumulus clouds above tend to increase many the albedo whereas that of stratocumulus clouds tend to lower It. Waterlogged surfaces show the lowest albedo values.